Convolution Operators and Bochner-Riesz Means on Herz-Type Hardy Spaces in the Dunkl Setting - A. Gasmi; F. Soltani (International Journal of Mathematics and Mathematical Sciences)
We study the Dunkl convolution operators on Herz-type Hardy spaces ℋα,2p and we establish a version of multiplier theorem for the maximal Bochner-Riesz operators on the Herz-type Hardy spaces ℋα,∞p.